Exercise training and DNA methylation profile in post-bariatric women: Results from an exploratory study - Nicoletti, Carolina F.; Roschel, Hamilton; Merege-Filho, Carlos; Lima, Alisson P.; Gil, Saulo; Pinhel, Marcela A. S.; Noronha, Natalia Y.; Santo, Marco A.; Jacome, Amalia; Crujeiras, Ana B.; Gualano, Bruno; Nonino, Carla B. (Frontiers in Sports and Active Living, 2023)
Exercise training and bariatric surgery have been shown to independently modulate DNA methylation profile in clusters of genes related to metabolic and inflammatory pathways. This study aimed to investigate the co-effects of a 6-month exercise training program and bariatric surgery on DNA methylation in women. In this exploratory, quasi-experimental study, we analyzed DNA methylation levels by array technology in eleven women who underwent Roux-en-Y Gastric Bypass and a 6-month, three-times-a-week, supervised exercise training program. Epigenome Wide Association Analysis showed 722 CpG sites with different methylation level equal to or greater than 5% (P<0.01) after exercise training. Some of these CpGs sites were related to pathophysiological mechanisms of inflammation, specially Th17 cell differentiation (FDR value<0.05 and P<0.001). Our data showed epigenetic modification in specific CpG sites related to Th17 cell differentiation pathway in post-bariatric women following a 6-months exercise training program.